A method for repairing surface defects of column cylinder body by using alloy cladding remanufacturing technology
By using cold arc cladding technology to form an alloy cladding layer on the surface of the column cylinder, the problems of poor adhesion and high cost of the cladding layer in the existing technology are solved, realizing efficient repair of the column cylinder and improving the service life and performance of the equipment.
Patent Information
- Application Number
- CN202211422026.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-14
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-11-14
AI Technical Summary
Existing alloy cladding technology, when repairing column cylinders, results in a thick cladding layer that is prone to porosity, spatter, welding defects, poor bonding strength, and high cost, making it difficult to meet the wear resistance and corrosion resistance requirements of column cylinders.
The cold arc cladding technology is adopted, using copper alloy welding wire and iron alloy welding wire coated with nanocomposite coating to form an alloy cladding layer on the sliding surface, outer circle, cylinder mouth and bottom valve hole of the column cylinder. By coating the welding wire with nanocomposite coating, the hardness and wear resistance of the cladding layer are improved, and the cladding process is optimized by controlling the arc parameters.
It improves the corrosion resistance and wear resistance of the column cylinder, extends its service life, reduces equipment procurement costs, and ensures that the performance of the repaired old equipment is no less than that of the new equipment, thereby improving asset utilization.
Smart Images

Figure BDA0003941945420000131 
Figure BDA0003941945420000132 
Figure BDA0003941945420000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy cladding, and in particular relates to a method for repairing surface defects of a column cylinder body by utilizing alloy cladding remanufacturing technology. Background Art
[0002] Hydraulic support is the main support equipment for the fully mechanized mining face of coal mines. It can reliably and effectively support and control the roof of the working face, prevent gangue from entering the mining face and push the conveyor. The hydraulic column cylinder is an important component of the hydraulic support. It is a pressure-bearing structural component used to control the pressure of the mining face. The pressure-bearing capacity and reliability of the column cylinder body often directly affect the working efficiency and safety of the mining face. In actual mining use, the column cylinder body is subjected to great pressure and a weakly acidic humid environment for a long time, and inevitably suffers from corrosion, strain, impact, and bumps, which cause local corrosion and coating damage to the column cylinder body, directly causing the hydraulic support to release pressure, greatly reducing the mining efficiency of the working face, and even safety accidents. Due to factors such as the long withdrawal and installation period of the hydraulic support and the lack of ground industrial space, the maintenance of the column cylinder body has always troubled and restricted the production progress and mining work of coal mines.
[0003] At present, the more mature repair technologies for the outer surface of the column cylinder body include electroplating chrome repair technology, plasma cladding repair technology and laser cladding technology. Electroplating chrome repair technology uses the principle of electrolytic ion replacement to reduce the metal ions in the plating solution into metal atoms and deposit them on the metal surface to form a repair layer with a certain thickness and high bonding force. This method has high repair efficiency and low cost, but it causes serious environmental pollution. Plasma cladding repair technology has a large heat input to the column cylinder body, which is prone to deformation. The overlap of the cladding layer is prone to slag inclusions and pores, but the process is stable and the cost is low. Laser cladding technology concentrates the energy of the column cylinder body, has a small heat input, and the workpiece has almost no deformation. The cladding layer has a smooth appearance, and the service life of laser cladding is longer than that of plasma cladding, but the equipment investment cost is high and the technical threshold is high.
[0004] Alloy cladding mainly adopts argon shielded welding repair technology, using pulse power supply, protective gas and special welding wire to complete the repair of workpieces. It has the characteristics of controlling the minimum welding heat input, less melting of base material, good arc stability, shallow melting depth, and fast cladding speed. The patent with application number CN201910942261.8 discloses a method for repairing and remanufacturing a hydraulic column guide sleeve. First, the surface of the guide sleeve is cleaned, and then the inner sealing surface of the guide sleeve is turned, and then the inner sealing surface of the guide sleeve is cold-melted with aluminum bronze welding wire. After the cladding is completed, the cladding quality is checked. The patent with application number CN202210423895.4 discloses a copper alloy cladding device for hydraulic cylinder wall for coal mines. The copper alloy welding wire is clad on the inner wall surface of the workpiece by low-temperature cold melting to achieve wear resistance and corrosion resistance. Although there have been related reports on the repair of column cylinder wall by cladding copper alloy, the existing copper melting process is limited by the cladding process and materials. The cladding layer is often thick and requires subsequent machining. Porosity, spatter, and welding defects are easily generated during the cladding process. In addition, the bonding strength between the cladding layer and the substrate is poor, and the performance of the alloy layer of the cladding layer needs to be improved. The inner wall of the column cylinder not only requires the cladding layer to have a suitable hardness, but also has high requirements for wear resistance and corrosion resistance to ensure the sealing of the cylinder. How to solve the column cylinder repair problem at a low cost and high efficiency is an urgent problem to be solved. Therefore, the development of alloy cladding strengthening and remanufacturing repair technology is of great practical significance for repairing the column cylinder of coal mine hydraulic support. Summary of the invention
[0005] Based on the deficiencies of the prior art, the present invention provides a method for repairing surface defects of a column cylinder body by utilizing alloy cladding remanufacturing technology, by cold arc cladding copper alloy welding wire on the sliding surface of the inner wall of the column cylinder body, and cold arc cladding iron alloy welding wire on the outer circle, cylinder mouth and bottom valve hole of the column cylinder body, so that the cladding layers in different parts meet the use requirements of the column cylinder body and improve the service life of the column cylinder body.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology comprises the following steps:
[0008] S1. Check the size and straightness of the disassembled column cylinder body, and then remove the original fatigue layer and pitting layer;
[0009] S2. Use sandblasting to adjust the outer surface quality, and use honing to finish the inner wall surface;
[0010] S3, using cold arc cladding wire to form alloy cladding layers on the inner wall sliding surface, outer circle, cylinder mouth and bottom valve hole of the column cylinder respectively;
[0011] S4. Finish and polish the column cylinder body according to the original size to meet the nominal size, tolerance and surface roughness requirements of the workpiece; perform flaw detection and repair welding on the alloy cladding layer;
[0012] S5. Heat the column cylinder after cold arc cladding to 720-740℃ in a furnace, keep it at this temperature for 2-2.5h, cool it to 500-550℃ and keep it at this temperature for 0.5-1.0h, cool it to 300℃ and then take it out of the furnace for air cooling;
[0013] S6. Conduct quality inspection on the column cylinder body;
[0014] Among them, the cold arc cladding wire used for the sliding surface of the inner wall of the column cylinder body in S3 is a copper alloy welding wire, and the cold arc cladding wire used for the outer circle of the column cylinder body, the cylinder mouth and the bottom valve hole is an iron alloy welding wire; the surface of the copper alloy welding wire and the surface of the iron alloy welding wire are both coated with a nano-composite coating, and the nano-composite coating is made of a coating liquid, and the coating liquid includes the following components in mass percentage: 5.4-7.2% intermetallic compound powder, 1.8%-3.6% nano-ceramic powder, 10-15% nano-conductive carbon black, 8-15% nickel-based alloy powder, 1-3% titanate accelerator, and the balance is base liquid.
[0015] The present invention cold-arc-clads the inner wall sliding surface of the column cylinder body with a copper alloy welding wire, so that the inner wall sliding surface has excellent wear resistance and corrosion resistance; cold-arc-clads the outer circle of the column cylinder body, the cylinder mouth and the bottom valve hole with an iron alloy welding wire, so that the outer circle, the cylinder mouth and the bottom valve hole have excellent hardness and strength; and by coating the copper alloy welding wire surface and the iron alloy welding wire surface with a nano-composite coating, the surface defects of the welding wire are reduced, the cladding surface quality is guaranteed, and the hard phase is introduced into the alloy cladding layer, so as to further improve the hardness and wear resistance of the alloy cladding layer.
[0016] Preferably, the copper alloy welding wire comprises the following components in mass percentage: Ni 4.5-6.0%, Al 7.0-9.0%, Fe2.2-4.0%, Mn 1.0-2.0%, Ti 0.2-0.35%, Gd 0.02-0.05%, As 0.02-0.04%, C<0.03%, and the balance is Cu; the ferroalloy welding wire comprises the following components in mass percentage: Ni 4.0-5.0%, Mo 2.0-3.0%, Cr17.0-19.0%, Mn 0.35-0.75%, Si 0.35-0.4%, C≤0.02%, P≤0.02%, S≤0.02%, and the balance is Fe.
[0017] The functions of the components in the copper alloy welding wire of the present invention are as follows:
[0018] Manganese (Mn) and aluminum (Al) have great solubility in copper. Appropriate amounts of manganese and aluminum can improve strength, hardness and corrosion resistance, while excessive amounts will reduce alloy plasticity. Nickel (Ni) is infinitely dissolved in aluminum bronze, which reduces organizational segregation, improves the toughness, corrosion resistance and thermal stability of the alloy. Nickel and iron (Fe) can refine grains, increase strength and refine grains. The iron content must be controlled below 4.0%, otherwise the alloy will become brittle, reduce toughness and corrosion resistance. Titanium (Ti) can inhibit the generation of pores and improve arc stability in high current areas. Gadolinium (Gd) can effectively reduce high-temperature flow stress, reduce grain size, and improve the ductility of the alloy; Arsenic (As) has a large solid solubility in copper and can eliminate the eutectic structure on the grain boundary of copper alloy, thereby improving the plasticity of copper; Titanium, gadolinium and arsenic are all added in trace amounts to synergistically help refine the structure and improve toughness. If the addition amount increases, too much dispersed high-melting-point intermetallic compounds will be formed. Although it can still improve the mechanical properties as a second phase, the discontinuous precipitation at the grain boundary will affect the cold working performance and easily cause the material to break or crack, which is not conducive to the processing of small-sized wires.
[0019] The functions of the components in the ferroalloy welding wire of the present invention are as follows:
[0020] Nickel (Ni) can improve the strength and corrosion resistance of ferroalloys while maintaining good plasticity and toughness; Molybdenum (Mo) can refine grains, improve hardenability and thermal strength, and enable ferroalloys to maintain sufficient strength and creep resistance at high temperatures; Chromium (Cr) can significantly improve strength, hardness, wear resistance and corrosion resistance, but will reduce plasticity and toughness, so the chromium content should not be too high; Manganese (Mn) can improve the hot working properties and mechanical properties of ferroalloys, but an increase in manganese will weaken corrosion resistance and welding performance, so the manganese content is controlled at 0. 75% or less; Silicon (Si) can significantly improve the tensile strength and yield ratio of the alloy, and has a good solid solution strengthening effect, but it will reduce the plasticity and ductility of the alloy, and will also deteriorate the weldability, so the silicon content is controlled at 0.35-0.4%; Carbon (C) and phosphorus (P) will increase the cold brittleness of the ferroalloy, and sulfur (S) will cause the ferroalloy to produce hot brittleness, all of which will reduce the ductility and toughness of the ferroalloy, and are not conducive to the welding performance of the ferroalloy welding wire, so the content of carbon, phosphorus and sulfur should be controlled below 0.02%.
[0021] Preferably, the intermetallic compound powder is in powder form (Ti 1-x Ta x )5Si3,(Ti 1-x Ta x)5Si3 wherein x is 0.2 to 0.4; the nano ceramic powder is Si3N4 powder with a particle size of 15 to 30 nm; the nickel-based alloy powder is nickel-based self-fluxing alloy powder; the titanate accelerator is n-butyl titanate; the base liquid is one or more of an alcohol solvent, an alcohol ether solvent, an ester solvent and a ketone solvent.
[0022] Further, the (Ti 1-x Ta x )5Si3 is prepared by the following steps: Ti powder, Ta powder and Si powder are weighed according to the molar ratio of the compounds, ball milled for 4 to 6 hours under a protective atmosphere, and cold isostatically pressed to obtain a block material; in a vacuum melting chamber, the block material is heated to melt, then cooled to 2100 to 2250°C and kept warm for 25 to 50 minutes, and powdered by gas atomization. After the powder is obtained, it is kept warm and tempered at 400 to 500°C for 2 to 4 hours under a protective atmosphere, then cooled to room temperature, and sieved to obtain (Ti 1- x Ta x )5Si3; wherein the protective atmosphere is argon, the ball-to-material ratio during ball milling is 8 to 15:1, anhydrous ethanol is used as a grinding aid, the ball milling speed is 300 to 400 r / min, and the ball milling is dried at 60 to 90°C after ball milling.
[0023] Preferably, the coating liquid is prepared by the following steps: under a protective atmosphere, intermetallic compound powder, nano-ceramic powder, nano-conductive carbon black and nickel-based alloy powder are mixed, and ball-milled for 2 to 4 hours to obtain a mixed powder; the mixed powder and a titanate accelerator are ultrasonically dispersed in a base liquid to obtain a coating liquid; wherein the protective atmosphere is a mixture of carbon dioxide and argon, the ball-to-material ratio during ball milling is 10 to 15:1, anhydrous ethanol is used as a grinding aid, the ball milling speed is 300 to 500 r / min, and the ball milling is dried at 60 to 90°C after ball milling.
[0024] Preferably, the nano-composite coating is prepared by the following steps: immersing the copper alloy welding wire / iron alloy welding wire in an etchant for surface treatment for 20 to 40 seconds, cleaning and drying, mechanically coating or electrostatically spraying the coating liquid on the surface of the copper alloy welding wire / iron alloy welding wire, drying, vacuum heat treatment at 380 to 480°C for 20 to 30 minutes, cooling with the furnace, and then winding to obtain the copper alloy welding wire / iron alloy welding wire coated with the nano-composite coating; wherein the etchant is a solution mixed with dilute sulfuric acid and citric acid, the mass percentage of H2SO4 in the etchant is 2 to 4%, and the mass percentage of citric acid is 3 to 5%.
[0025] Furthermore, the diameter of the cold arc cladding wire is 1.0-3.0 mm, and the mass percentage of the nano-composite coating in the cold arc cladding wire is 0.5-1%.
[0026] The functions of the components in the nanocomposite coating of the present invention are as follows:
[0027] (Ti 1-x Ta x )5Si3 and Si3N4 are wrapped on the welding wire in the form of a surface nano-composite coating, which has a protective effect on the welding wire, has a lubricating effect on the wire feeding during the processing, and reduces the surface defects of the welding wire. After arc melting, (Ti 1-x Ta x )5Si3 and Si3N4 exist as hard phases in the alloy cladding layer, which can significantly improve the hardness and wear resistance of the material; the nickel-based self-fluxing alloy powder has a low melting point, has a repairing effect on the surface of the welding wire matrix, plays a connecting role in the combination of various phases in the cladding, and improves the density of the material; n-butyl titanate, as a metal adhesion promoter, can effectively improve the adhesion of other powders on the welding wire matrix, and after high-temperature decomposition, it forms titanium dioxide, which will cause the anode spots on the surface of the workpiece to shrink and the arc to shrink, and the surface tension gradient of the molten pool will change, which will play a role in refining the molten droplets and improving the arc stability, reducing spatter and improving the deposition efficiency; nano-conductive carbon black has good fluidity and high-temperature lubricity, which is conducive to the dispersion uniformity of the coating liquid, ensuring the conductivity and wire feeding stability during the use of the welding wire, and nano-conductive carbon black forms carbon oxides during cladding, which further protects the alloy cladding layer and improves the surface quality of the cladding.
[0028] Among them, the (Ti 1-x Ta x )5Si3 is prepared by mechanical ball milling combined with gas atomization. Ball milling makes the material have larger surface energy and lattice distortion energy, which can promote the diffusion of atoms, the solid solution of alloys, and the migration and elimination of pores at a lower temperature, so as to form a solid solution during smelting and reduce the generation of complex phases; gas atomization makes the material have low oxygen content, good powder sphericity, and appropriate particle size. Insulation and tempering under a protective atmosphere are helpful to improve the organization and make the composition uniform. The present invention adjusts the surface roughness through weak etching to improve the adhesion of the coating, then applies the coating liquid to the surface, and finally performs medium-temperature heat treatment to stabilize the nano-composite coating, thereby achieving uniformity and stabilization of the welding wire composition.
[0029] Preferably, when repairing the sliding surface of the inner wall of the column cylinder, the average arc voltage of cold arc cladding is 12-25V, the output pulse current is 20-90A, the output pulse time is 40-60ms, the wire feeding speed is 2.0-3.0m / min, the cladding line speed is 0.6-1.2m / min, the cladding thickness is 0.5-3mm, and the protective gas is argon with a flow rate of 8-15L / min.
[0030] Preferably, when repairing the outer circle of the column cylinder, the cylinder mouth and the bottom valve hole, the average arc voltage of cold arc cladding is 12-25V, the output pulse current is 50-100A, the output pulse time is 40-60ms, the wire feeding speed is 4.0-5.0m / min, the cladding line speed is 2.0-2.5m / min, the cladding thickness is 0.5-4mm, and the protective gas is argon with a flow rate of 8-15L / min.
[0031] Preferably, the outer cylindrical surface quality after sandblasting in S2 reaches Sa2.5, and the inner wall surface roughness after honing is Ra≤0.4μm; and the surface roughness after polishing in S4 is Ra≤0.2μm.
[0032] The present invention repairs the surface defects of the hydraulic support cylinder body by cold arc cladding, and the formed alloy cladding layer is well bonded with the substrate to be clad, thereby improving the corrosion resistance and wear resistance of the column cylinder body, being able to better exert the performance of the hydraulic support column, and increasing the service life of the column underground; after the old column cylinder body is repaired and remanufactured, it is no less than new equipment in terms of size, shape, life and performance, thereby improving asset utilization, extending the life cycle of equipment use, and reducing the purchase cost of equipment. DETAILED DESCRIPTION
[0033] In order to make the technical purpose, technical scheme and beneficial effects of the present invention clearer, the technical scheme of the present invention is further described below in conjunction with specific embodiments. However, the embodiments are intended to explain the present invention and cannot be understood as limiting the present invention. The raw materials used in the embodiments are all common commercially available products. If no specific technology or conditions are specified, the technology or conditions described in the literature in the field or the product instructions shall be followed.
[0034] A method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology comprises the following steps:
[0035] S1. Check the size and straightness of the disassembled column cylinder body, and then remove the original fatigue layer and pitting layer;
[0036] S2. Use sandblasting to adjust the outer surface quality to Sa2.5, and use honing to finish the inner wall surface to make the roughness Ra≤0.4μm;
[0037] S3, using cold arc cladding wire to form alloy cladding layers on the inner wall sliding surface, outer circle, cylinder mouth and bottom valve hole of the column cylinder respectively;
[0038] S4. Finish and polish the column cylinder body according to the original size to meet the nominal size, tolerance and surface roughness requirements of the workpiece (Ra≤0.2μm); perform flaw detection and repair welding on the alloy cladding layer;
[0039] S5. The column cylinder body after cold arc cladding is placed in a furnace and heated to 730°C, kept at this temperature for 2 hours, then cooled to 510°C and kept at this temperature for 1 hour, and then cooled to 300°C and air-cooled;
[0040] S6. Perform quality inspection on the column cylinder body.
[0041] Among them, when repairing the sliding surface of the outer wall of the column cylinder, the average arc voltage of the cold arc cladding is 20V, the output pulse current is 60A, the output pulse time is 50ms, the wire feeding speed is 3m / min, the cladding line speed is 1m / min, and the shielding gas is argon with a flow rate of 10L / min; there is no preheating before welding, and natural air cooling after welding. When repairing the outer circle, cylinder mouth and bottom valve hole of the column cylinder, the average arc voltage of the cold arc cladding is 20V, the output pulse current is 80A, the output pulse time is 50ms, the wire feeding speed is 5.0m / min, the cladding line speed is 2.5m / min, and the shielding gas is argon with a flow rate of 10L / min; there is no preheating before welding, and natural air cooling after welding.
[0042] In the following embodiments, the diameter reduction rate is: Deformation:
[0043] In the formula of diameter reduction rate and deformation amount, D0 is the diameter of the rolling / die (unit: mm), D i It is the rolling / die diameter (unit: mm).
[0044] Example 1
[0045] In S3 of the above method, copper alloy welding wire is used for the cold arc cladding wire of the sliding surface of the inner wall of the column cylinder body, and iron alloy welding wire is used for the cold arc cladding wire of the outer circle of the column cylinder body, the cylinder mouth and the bottom valve hole. The surfaces of the copper alloy welding wire and the iron alloy welding wire are both coated with a nano-composite coating, and the mass percentage of the nano-composite coating in the cold arc cladding wire (the total mass of the copper alloy welding wire / iron alloy welding wire and the nano-composite coating) is 0.8%.
[0046] The preparation steps of the copper alloy welding wire are as follows:
[0047] (1) The ingredients are prepared according to the mass percentage of each component: Ni 5.2%, Al 8.1%, Fe 2.8%, Mn 1.37%, Ti 0.28%, Gd 0.03%, As 0.03%, C < 0.03%, and the balance is Cu; wherein Ni / Fe = 1.857, and the raw materials can be pure metals or intermediate alloys;
[0048] (2) Melting: The raw materials are placed in a vacuum melting chamber, heated to 1100°C by medium frequency induction, and melted for 45 minutes to obtain an alloy melt. Argon gas is introduced into the alloy melt for 15 minutes under a heat preservation state to obtain a copper alloy liquid;
[0049] (3) Casting-hot rolling: The copper alloy liquid obtained in step (2) is heated to 1300° C. and horizontally continuously cast to form a copper alloy rod with a diameter of 40 mm. The rolling temperature is controlled to be 450° C. and hot rolling is performed three times. The total outer diameter reduction rate of the hot rolling is 75% and the rolling speed is 2 m / s. The surface is then pickled to remove oil stains and impurities on the surface to obtain a copper alloy rod with a diameter of 10 mm.
[0050] (4) Solution-aging treatment: In a vacuum furnace, the copper alloy rod is heated to 910°C, kept at this temperature for 1.5 hours, cooled to below 60°C in a quenching medium, and then air-cooled to room temperature; then heated to 440°C in a vacuum furnace, kept at this temperature for 2 hours, cooled to below 100°C in the furnace, and then air-cooled to room temperature to obtain a solution-strengthened rod;
[0051] (5) Phosphating treatment - cold drawing - intermediate annealing: the solid solution strengthened rod obtained in step (4) is straightened, pickled, surface phosphating treated and lubricated, and then single-mode drawing is performed, with a diameter reduction rate of 17% and a drawing speed of 1 m / s for each pass, and then multi-mode drawing is performed, with a diameter reduction rate of 10% and a drawing speed of 2 m / s for each pass. When the cold deformation amount reaches 60-75% (total diameter reduction rate>40%) during the single-mode drawing and multi-mode drawing processes, vacuum annealing is performed at 560°C for 30 min and furnace cooling is performed. No vacuum annealing treatment is performed at the end of the multi-mode drawing. After cold drawing, sizing and scraping (scraping speed is 8 m / s, diameter reduction is 0.02 mm) are performed to obtain a copper alloy welding wire with a diameter of 1 mm (since vacuum heat treatment is performed when preparing the nano-composite coating, no annealing treatment is performed after machining);
[0052] The pickling was carried out with an aqueous solution containing 100 g / L H2SO4, 40 g / L H2O2, 40 g / L ethanol and 0.2 g / L benzotriazole, and the surface was immersed at room temperature for 30 seconds. The surface phosphating was carried out with a common commercially available zinc-manganese phosphating solution (AIR-XMA50), and the surface was immersed at room temperature for 5 minutes. After the surface phosphating, the phosphating film weight per unit area was about 5 g / m 2 ;
[0053] The cold drawing and intermediate annealing process is controlled as follows:
[0054] Single-mode drawing: φ10mm→φ8.30mm→φ6.89mm→φ5.72mm→intermediate annealing→φ4.75mm→φ3.94mm→φ3.27mm→intermediate annealing;
[0055] Multi-mode drawing: φ3.27mm—φ2.94mm—φ2.65mm—φ2.38mm—φ2.14mm—φ1.93mm; intermediate annealing; φ1.93mm—φ1.74mm—φ1.56mm—φ1.40mm—φ1.26mm—φ1.13mm—φ1.02mm.
[0056] The yield strength of the copper alloy welding wire prepared above is 789.6 MPa and the tensile strength is 1237.1 MPa.
[0057] The preparation steps of the ferroalloy welding wire are as follows:
[0058] (1) The ingredients are prepared according to the mass percentage of each component: Ni 4.5%, Mo 2.5%, Cr 18.0%, Mn 0.6%, Si 0.38%, C ≤ 0.02%, P ≤ 0.02%, S ≤ 0.02%, and the balance is Fe; the raw materials can be pure metals or intermediate alloys;
[0059] (2) Melting: The raw materials are placed in a vacuum melting chamber, heated to 1350°C by medium frequency induction, and melted for 45 minutes to obtain an alloy melt. Argon gas is introduced into the alloy melt for 15 minutes under a heat preservation state to obtain a ferroalloy liquid;
[0060] (3) Casting-hot rolling: The ferroalloy liquid is controlled at 1300-1350°C, and is horizontally continuously cast to form a ferroalloy bar with a diameter of 40 mm. The rolling temperature is controlled at 450°C, and hot rolling is performed three times. The total outer diameter reduction rate of the hot rolling is 75%, and the hot rolling speed is 2 m / s. Then, the surface is pickled to remove oil and impurities on the surface, and a ferroalloy rod with a diameter of 10 mm is obtained.
[0061] (4) Full annealing: In a vacuum furnace, the ferroalloy rod is heated to 950°C, kept at this temperature for 1 hour, cooled to below 450°C, and then air-cooled to room temperature to obtain a refined rod;
[0062] (5) Cold drawing-intermediate annealing: After straightening, cleaning and lubricating the thinned rod, it is subjected to multi-pass drawing, with a diameter reduction rate of 8-10% and a drawing speed of 1 m / s for each pass. When the cold deformation during the drawing process is greater than 65%, it is vacuum annealed at 590°C for 30 min and cooled with the furnace. No annealing treatment is performed at the end of the drawing. After cold drawing, it is sized and scraped (scraping speed is 8 m / s, scraping is 2 times, and the diameter reduction is 0.02 mm for each pass) to obtain an iron alloy welding wire with a diameter of 2 mm (since vacuum heat treatment is performed when preparing the nano-composite coating, no annealing treatment is performed after machining);
[0063] The cold drawing and intermediate annealing process is controlled as follows:
[0064] φ10mm→φ9.0mm→φ8.1mm→φ7.29mm→φ6.56mm→φ5.90mm→intermediate annealing→φ5.31mm→φ4.78mm→φ4.30mm→φ3.87mm→φ3.48mm→intermediate annealing→φ3.13mm→φ2.88mm→φ2.62mm→φ2.41mm→φ2.22mm→φ2.04mm.
[0065] The yield strength of the ferroalloy welding wire prepared above is 1012.3 MPa and the tensile strength is 1756.9 MPa.
[0066] The nanocomposite coating is made of a coating liquid, and the coating liquid includes the following components in percentage by mass: (Ti 0.75 Ta 0.25 )5Si3 powder 5.8%, nano Si3N4 powder 2.7%, nano conductive carbon black 12.5%, Ni60A powder 12%, n-butyl titanate 2%, and the balance is isopropyl alcohol.
[0067] Among them, the (Ti 0.75 Ta 0.25 )5Si3 is prepared by the following steps:
[0068] Ti powder, Ta powder and Si powder were weighed according to the molar ratio of the compounds, and ball-milled for 5 h in an argon atmosphere (the ball-to-material ratio was 10:1 during ball milling, anhydrous ethanol was used as a grinding aid, the ball milling speed was 400 r / min, and the powder was dried at 80°C after ball milling), and cold isostatic pressing was performed to obtain a block material; in a vacuum melting chamber (the vacuum degree was less than 0.1 Pa), the block material was heated to melt, then cooled to 2180°C and kept warm for 40 min, and powdered by gas atomization (using argon powder spraying at a pressure of 4 MPa). After the powder was obtained, it was kept warm and tempered at 450°C for 3 h in an argon atmosphere, then cooled to room temperature, and sieved to obtain the powder.
[0069] The coating solution is prepared by the following steps:
[0070] In a mixed atmosphere of carbon dioxide and argon, (Ti 0.75 Ta 0.25 )5Si3 powder, nano Si3N4 powder (particle size of about 20nm), nano conductive carbon black and Ni60A powder are mixed and ball-milled for 4h (the ball-to-material ratio during ball milling is 12:1, anhydrous ethanol is used as a grinding aid, the ball milling speed is 400r / min, and the ball mill is dried at 70°C after ball milling) to obtain a mixed powder; the mixed powder and n-butyl titanate are ultrasonically dispersed in isopropanol to obtain a coating liquid.
[0071] The steps for forming a nanocomposite coating on the surface of copper alloy welding wire / iron alloy welding wire are as follows:
[0072] The copper alloy welding wire / iron alloy welding wire is immersed in an etchant (aqueous solution containing 3% H2SO4 and 4% citric acid) for surface treatment for 20 to 30 seconds (30 seconds for copper alloy welding wire and 20 seconds for iron alloy welding wire). After cleaning and drying, the coating liquid is mechanically coated on the surface of the copper alloy wire. After drying, it is vacuum heat treated for 30 minutes (400°C for copper alloy welding wire and 450°C for iron alloy welding wire). After cooling with the furnace, it is rewound to obtain a copper alloy welding wire / iron alloy welding wire coated with a nano-composite coating. The nano-composite coating improves the lubricity of the cold arc cladding wire and reduces the wear of the cold arc cladding wire on the conductive nozzle. The copper alloy welding wire / iron alloy welding wire coated with the nano-composite coating significantly reduces the wear rate of the conductive nozzle aperture ( Where D0 is the aperture value of the conductive nozzle before use, D max The maximum diameter of the conductive tip after use). After continuous cold arc cladding for 5 hours, the wear rate of the conductive tip by the copper alloy welding wire and the ferroalloy welding wire was about 18% and 21% respectively, and the wear rate of the conductive tip by the copper alloy welding wire / ferroalloy welding wire coated with nano-composite coating was no more than 11%.
[0073] Copper alloy welding wire / iron alloy welding wire coated with nano-composite coating is cold arc clad on the column cylinder body (main material: 27SiMn), and the bonding force is greater than 300MPa. The surface hardness of the cladding layer at the sliding surface of the inner wall of the column cylinder body is about 486HV on average, and the surface hardness of the cladding layer on the outer circle, cylinder mouth and bottom valve hole of the column cylinder body is about 603HV on average. The inner wall and outer circle cladding layers of the column cylinder body are resistant to neutral salt spray corrosion for more than 1000h.
[0074] Since the sealing performance of the inner wall of the cylinder directly affects the service life of the cylinder, the material used for the inner wall of the cylinder needs to have excellent wear resistance and corrosion resistance in addition to good hardness. The cold arc cladding wire material of the inner wall of the cylinder is further studied and compared from Examples 2 to 5 and Comparative Examples 1 to 3.
[0075] Example 2
[0076] According to the technical solution of Example 1, the difference is:
[0077] The copper alloy welding wire comprises the following components in mass percentage: Ni 5.6%, Al 8.1%, Fe 2.8%, Mn 1.37%, Ti 0.28%, Gd 0.03%, As 0.03%, C < 0.03%, and the balance is Cu; wherein Ni / Fe = 2.0.
[0078] Compared with Example 1, the difference of Example 2 is that the Ni content in the copper alloy welding wire is changed, and Ni / Fe changes accordingly.
[0079] Example 3
[0080] According to the technical solution of Example 1, the difference is:
[0081] The copper alloy welding wire comprises the following components in mass percentage: Ni 5.2%, Al 8.1%, Fe 3.47%, Mn 1.37%, Ti 0.28%, Gd 0.03%, As 0.03%, C < 0.03%, and the balance is Cu; wherein Ni / Fe = 1.5.
[0082] Compared with Example 1, the difference of Example 3 is that the Fe content in the copper alloy welding wire is changed, and Ni / Fe changes accordingly.
[0083] Example 4
[0084] According to the technical solution of Example 1, the difference is that the mass percentage of the nano-composite coating in the cold arc cladding wire is 0.5%.
[0085] Compared with Example 1, the difference of Example 4 is that the mass percentage of the nano-composite coating in the cold arc cladding wire is reduced.
[0086] Example 5
[0087] According to the technical solution of Example 1, the difference is that the mass percentage of the nano-composite coating in the cold arc cladding wire is 1.0%.
[0088] Compared with Example 1, the difference of Example 5 is that the mass percentage of the nano-composite coating in the cold arc cladding wire is increased.
[0089] Comparative Example 1
[0090] A cold arc cladding wire (without nanocomposite coating) comprises the following components in mass percentage: Ni 5.2%, Al 8.1%, Fe 5.2%, Mn 1.37%, Ti 0.28%, Gd 0.03%, As 0.03%, C < 0.03%, and the balance is Cu; wherein Ni / Fe = 1.0.
[0091] Compared with the copper alloy welding wire of Example 1, the difference of Comparative Example 1 is that the Fe content is increased and Ni / Fe changes accordingly.
[0092] Comparative Example 2
[0093] A cold arc cladding wire (without nanocomposite coating) comprises the following components in mass percentage: Ni 5.2%, Al 8.1%, Fe 2.0%, Mn 1.37%, Ti 0.28%, Gd 0.03%, As 0.03%, C < 0.03%, and the balance is Cu; wherein Ni / Fe = 2.6.
[0094] Compared with the copper alloy welding wire of Example 1, the difference of Comparative Example 2 is that the Fe content is reduced and Ni / Fe is changed accordingly.
[0095] Comparative Example 3
[0096] A cold arc cladding wire material has a copper alloy welding wire / iron alloy welding wire as a substrate, the surface of the substrate is coated with a nano-composite coating, and the mass percentage of the nano-composite coating in the nickel-aluminum bronze welding wire is 2%; the substrate and the nano-composite coating are prepared according to the technical solution of Example 1.
[0097] Compared with Example 1, the difference of Comparative Example 3 is that the mass percentage of the nano-composite coating in the cold arc cladding wire is increased.
[0098] In order to detect the performance of the cold arc cladding wire used for the sliding surface of the cylinder body wall, the cold arc cladding wire was clad on the 30CrMnSi steel plate substrate (the surface was polished and cleaned) according to the above cold arc cladding parameters, and the bonding strength, surface average hardness, elongation and friction and wear of the cladding layer were tested (using a friction and wear testing machine, test parameters: room temperature, speed 150r / min, working load 50N, duration 10min). The results are shown in Table 1.
[0099] Table 1 Performance of the cold arc cladding wire (copper alloy welding wire) described in Examples 1 to 5 and Comparative Examples 1 to 3
[0100]
[0101] It can be seen from Table 1 that in order to take into account both toughness and hardness, Ni / Fe should be 1.5-2.0. Increasing the relative content of Fe will reduce toughness, and reducing the content of Fe to a certain extent will no longer increase toughness, but reduce hardness. The mass percentage of nanocomposite coating in cold arc cladding wire should be controlled at 0.5-1%. Too little will not work, and too much will deteriorate the material, resulting in a decrease in the bonding force between the alloy cladding layer and the substrate to be clad.
[0102] The corrosion resistance of the cladding layers formed by the cold arc cladding wires described in Example 1 and Comparative Examples 1 to 3 was tested using a salt spray tester. The test conditions are shown in Table 2.
[0103] Table 2 Corrosion resistance test conditions
[0104]
[0105]
[0106] After testing, the cladding layer formed by the cold arc cladding wire described in Example 1 had no rust spots after 1000 hours of neutral salt spray test and 120 hours of copper accelerated acetic acid salt spray test. The cladding layer formed by the cold arc cladding wire described in Comparative Examples 1 and 2 had more than 2 rust spots after 120 hours of copper accelerated acetic acid salt spray test. The cladding layer formed by the nickel aluminum bronze welding wire described in Comparative Example 3 had 1 rust spot after 120 hours of copper accelerated acetic acid salt spray test.
[0107] In summary, the present invention repairs the surface defects of the hydraulic support column cylinder body by cold arc cladding, and the formed alloy cladding layer is well bonded with the substrate to be clad, and has high hardness and good wear resistance and corrosion resistance.
[0108] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology, characterized in that: The following steps are involved: S1. Check the size and straightness of the disassembled column cylinder body, and then remove the original fatigue layer and pitting layer; S2. Use sandblasting to adjust the surface quality of the outer circle, and use honing to finish the inner wall surface; S3, using cold arc cladding wire to form alloy cladding layers on the inner wall sliding surface, outer circle, cylinder mouth and bottom valve hole of the column cylinder respectively; S4. Finish and polish the column cylinder body according to the original size to meet the nominal size, tolerance and surface roughness requirements of the workpiece; perform flaw detection and repair welding on the alloy cladding layer; S5. Load the column cylinder after cold arc cladding into the furnace, heat it to 720~740℃, keep it warm for 1.5~2.0 h, cool it to 500~550℃ and keep it warm for 0.5~1.0 h, cool it to 300℃ and then take it out of the furnace for air cooling; S6. Conduct quality inspection on the column cylinder body; Among them, the cold arc cladding wire used for the sliding surface of the inner wall of the column cylinder in S3 is a copper alloy welding wire, and the cold arc cladding wire used for the outer circle of the column cylinder, the cylinder mouth and the bottom valve hole is an iron alloy welding wire; the surface of the copper alloy welding wire and the surface of the iron alloy welding wire are both coated with a nano-composite coating, and the mass percentage of the nano-composite coating in the cold arc cladding wire is 0.5~1%; The copper alloy welding wire comprises the following components in mass percentage: Ni 4.5-6.0%, Al 7.0-9.0%, Fe 2.2-4.0%, Mn 1.0-2.0%, Ti 0.2-0.35%, Gd 0.02-0.05%, As 0.02-0.04%, C<0.03%, and the balance is Cu; the ferroalloy welding wire comprises the following components in mass percentage: Ni 4.0-5.0%, Mo 2.0-3.0%, Cr 17.0-19.0%, Mn 0.35-0.75%, Si 0.35-0.4%, C≤0.02%, P≤0.02%, S≤0.02%, and the balance is Fe; The nanocomposite coating is made of a coating liquid, which includes the following components in mass percentage: 5.4-7.2% intermetallic compound powder, 1.8%-3.6% nano ceramic powder, 10-15% nano conductive carbon black, 8-15% nickel-based alloy powder, 1-3% titanate accelerator, and the balance is base liquid; The intermetallic compound powder is in powder form (Ti 1-x Ta x )5Si3,(Ti 1-x Ta x )5Si3 wherein x is 0.2-0.4; the nano ceramic powder is Si3N4 powder with a particle size of 15-30 nm; the nickel-based alloy powder is nickel-based self-fluxing alloy powder; the titanate accelerator is n-butyl titanate; the base liquid is one or more of an alcohol solvent, an alcohol ether solvent, an ester solvent and a ketone solvent.
2. The method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology according to claim 1, characterized in that: When repairing the sliding surface of the inner wall of the column cylinder, the average arc voltage of cold arc cladding is 12~25 V, the output pulse current is 20~90 A, the output pulse time is 40~60 ms, the wire feeding speed is 2.0~3.0 m / min, the cladding line speed is 0.6~1.2 m / min, the cladding thickness is 0.5~3 mm, and the protective gas is argon with a flow rate of 8~15 L / min.
3. The method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology according to claim 1, characterized in that: When repairing the outer circle of the column cylinder, the cylinder mouth and the bottom valve hole, the average arc voltage of cold arc cladding is 12~25 V, the output pulse current is 50~100 A, the output pulse time is 40~60 ms, the wire feeding speed is 4.0~5.0 m / min, the cladding line speed is 2.0~2.5 m / min, the cladding thickness is 0.5~4 mm, and the protective gas is argon with a flow rate of 8~15 L / min.
4. The method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology according to claim 1 is characterized in that: The 1-x Ta x )5Si3 is prepared by the following steps: Ti powder, Ta powder and Si powder are weighed according to the molar ratio of the compounds, ball milled for 4-6 hours under a protective atmosphere, and cold isostatically pressed to obtain a block material; in a vacuum melting chamber, the block material is heated to melt, then cooled to 2100-2250℃ and kept warm for 25-50 min, and powdered by gas atomization. After the powder is obtained, it is kept warm and tempered at 400-500℃ for 2-4 hours under a protective atmosphere, then cooled to room temperature, and sieved to obtain (Ti 1-x Ta x )5Si3; wherein the protective atmosphere is argon, the ball-to-material ratio during ball milling is 8~15:1, anhydrous ethanol is used as a grinding aid, the ball milling speed is 300~400 r / min, and the ball milling is dried at 60~90°C after ball milling.
5. The method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology according to claim 1 is characterized in that: The coating liquid is prepared by the following steps: under a protective atmosphere, intermetallic compound powder, nano-ceramic powder, nano-conductive carbon black and nickel-based alloy powder are mixed, and ball milling is performed for 2-4 hours to obtain a mixed powder; the mixed powder and a titanate accelerator are ultrasonically dispersed in a base liquid to obtain a coating liquid; wherein the protective atmosphere is a mixture of carbon dioxide and argon, the ball-to-material ratio during ball milling is 10-15:1, anhydrous ethanol is used as a grinding aid, the ball milling speed is 300-500 r / min, and the ball milling is dried at 60-90°C after ball milling.
6. The method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology according to claim 1 is characterized in that: The nano composite coating is prepared by the following steps: immersing the copper alloy welding wire / iron alloy welding wire in an etchant for surface treatment for 20-40 seconds, cleaning and drying, mechanically coating or electrostatically spraying the coating liquid on the surface of the copper alloy welding wire / iron alloy welding wire, drying, vacuum heat treatment at 380-480°C for 20-30 minutes, cooling with the furnace, and then winding to obtain the copper alloy welding wire / iron alloy welding wire coated with the nano composite coating; wherein the etchant is a solution mixed with dilute sulfuric acid and citric acid, the mass percentage of H2SO4 in the etchant is 2-4%, and the mass percentage of citric acid is 3-5%.
7. The method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology according to claim 6 is characterized in that: The diameter of the cold arc cladding wire is 1.0-3.0 mm.
8. The method for repairing the surface defects of a column cylinder body by using alloy cladding remanufacturing technology according to claim 1 is characterized in that: After sandblasting in S2, the surface quality of the outer circle reaches Sa2.5, and the surface roughness of the inner wall after honing is Ra≤0.4 μm; after polishing in S4, the surface roughness is Ra≤0.2 μm.
Citation Information
Patent Citations
Method for repairing and remanufacturing guide sleeve of hydraulic stand column
CN110695608A
Device for cladding copper alloy on wall of hydraulic cylinder for coal mine
CN114855164A
Copper-zinc alloy, method for its manufacture and use
EP2009122A1
Wear-resistant and corrosion-resistant iron-based alloy powder for laser cladding and laser cladding layer thereof
JP6896138B1